Alcohol use disorder and non‐fatal suicide attempt: findings from a Swedish National Cohort Study. (12th July 2021) - Edwards, Alexis C.; Ohlsson, Henrik; Mościcki, Eve; Crump, Casey; Sundquist, Jan; Kendler, Kenneth S.; Sundquist, Kristina
Abstract: Background and Aims: Alcohol use disorder (AUD) is associated with increased risk of non‐fatal suicide attempt. We aimed to measure the strength and mechanistic nature of the association between AUD and increased suicide attempt and determine any causal pathways and/or shared risk factors. Design: We used Cox proportional hazards models in population‐level and co‐relative analyses to evaluate the risk of first non‐fatal suicide attempt as a function of previous AUD. Setting and Participants: We used continuously updated longitudinal nationwide Swedish registry data on native Swedes born from 1950 to 1970 ( n = 2 229 619) and followed from age 15 until 2012. Measurements: AUD and suicide attempt were identified using International Classification of Diseases (ICD)‐8, ICD‐9, and ICD‐10 codes. AUD was also identified using pharmacy and criminal records. Genetic and family environmental risks were derived based on relatedness via the Multi‐Generation Register and shared residency via the Population and Housing Census and the Total Population Register. Findings: AUD was robustly associated with suicide attempt in crude models (hazard ratio [HR] = 15.24 [95% CI: 14.92, 15.56]). In models adjusted for sociodemographic factors and psychiatric comorbidity, the association was attenuated: for women, HRs declined gradually across time, ranging from 5.55 (3.72, 8.29) during the observation period that ranged from age 15 to 19 years to 1.77 (1.65, 1.90) at age 40 or older. For men, the corresponding figures were 6.12 (4.07, 9.19) and 1.83 (1.72, 1.94); in contrast to women, risk of suicide attempt among men increased from age 15 to 29 before declining. In co‐relative models, a residual association remained, consistent with a causal path from AUD to suicide attempt. Conclusions: In Sweden, alcohol use disorder appears to be an important predictor of suicide attempt even in the context of other psychiatric disorders. The observed association is likely the result of features that jointly impact risk of alcohol use disorder and suicide attempts (genetic liability, psychiatric illness, and childhood stressors) and a potentially causal pathway, acting independently or in conjunction with one another.